Narrativas Sobre El Proyecto De Vida En Mujeres Empleadas Que Asumen Su Condición De Madresolterismo (2019)
The general objective of this research was to determine the adjustments of the life project in women in the condition of mothers and mothers from their narratives. It is a descriptive, qualitative study, with a symbolic interactionist perspective in which five single mothers participated. They were interviewed in a semi-structured interview where the needs and aspirations regarding the life project were addressed. The analysis of results allowed to demonstrate that in the project of life of the participants there were different adjustments and modifications after assuming the condition of motherlessness, experiencing different sensations and feelings of self-discovery